Cerrahi Alan Enfeksiyonları - Dikmen, Kürşat (Genel Cerrahi Staj Dersleri, 2024)
Cerrahi alan enfeksiyonları (CAE), cerrahi müdahaleler sonrası ortaya çıkan ve ciddi komplikasyonlara yol açabilen önemli bir sağlık sorunudur. Enfeksiyonların önlenmesi için cerrahi tekniklerin yanı sıra, hastanın fizyolojik yönetimi ve antimikrobiyal profilaksi büyük önem taşır. Enfeksiyonun türüne bağlı olarak, cerrahi müdahale ve uygun antibiyotik tedavisi gereklidir. Ayrıca, hastane kaynaklı patojenlerde artan antibiyotik direnci, enfeksiyonların tedavisinde zorluklar yaratmaktadır. Surgical site infections (SSIs) are significant complications that can arise after surgical procedures, leading to severe health issues. Preventive measures, including proper surgical techniques, patient management, and antimicrobial prophylaxis, are crucial in reducing the risk of infection. Depending on the type of infection, surgical intervention and appropriate antibiotic therapy may be required. Additionally, the increasing antibiotic resistance in hospital-acquired pathogens presents challenges in treating these infections.